Establishing reproductive potential and advances in fertility preservation techniques for XY individuals with differences in sex development - Islam, R; Lane, S; Williams, S; Becker, C; Conway, G; Creighton, S (Wiley, 2019)
Background Discordance between gonadal type and gender identity has often led to an assumption of infertility in patients with differences in sex development (DSD). However, there is now greater recognition of fertility being an important issue for this group of patients. Currently, gonadal tissue that may have fertility potential is not being stored for individuals with DSD and, where gonadectomy forms part of management, is often discarded. The area of fertility preservation has been predominantly driven by oncofertility which is a field dedicated to preserving the fertility of patients undergoing gonadotoxic cancer treatment. The use of fertility preservation techniques could be expanded to include individuals with DSD where functioning gonads are present. Methods This is a systematic literature review evaluating original research articles and relevant reviews between 1974 and 2018 addressing DSD and fertility, in vitro maturation of sperm, and histological/ultrastructural assessment of gonadal tissue in complete and partial androgen insensitivity syndrome, 17β‐hydroxysteroid dehydrogenase type 3 and 5α‐reductase deficiency. Conclusion Successful clinical outcomes of ovarian tissue cryopreservation are paving the way for similar research being conducted using testicular tissue and sperm. There have been promising results from both animal and human studies leading to cryopreservation of testicular tissue now being offered to boys prior to cancer treatment. Although data are limited, there is evidence to suggest the presence of reproductive potential in the gonads of some individuals with DSD. Larger, more detailed studies are required, but if these continue to be encouraging, individuals with DSD should be given the same information, opportunities and access to fertility preservation as other patient groups.